Agricultural trade and food policy : the experience of five developing countries - Bale, Malcolm D. (Washington, D.C., U.S.A. : World Bank, 1985)
This essay reviews and generalizes recent World Bank studies on agricultural pricing and trade policy in developing countries
Bibliography: p. 39-40.
osc 25/08/2021
Loans
Keywords: Agriculture and state; Produce trade; Food supply